Minimal-gain-printed silicon nanolaser - Park, Byoung Jun; Kim, Min-Woo; Park, Kyong-Tae; Kim, Hwi-Min; You, Byeong Uk; Yu, Aran; Kim, Jin Tae; No, You-Shin; Kim, Myung-Ki (American Association for the Advancement of Science, 2024)
While there have been notable advancements in Si-based optical integration, achieving compact and efficient continuous-wave (CW) III-V semiconductor nanolasers on Si at room temperature remains a substantial challenge. This study presents an innovative approach: the on-demand minimal-gain-printed Si nanolaser. By using a carefully designed minimal III-V optical gain structure and a precise on-demand gain-printing technique, we achieve lasing operation with superior spectral stability under pulsed conditions and observe a strong signature of CW operation at room temperature. These achievements are attributed to addressing both fundamental and technological issues, including carrier diffusion, absorption loss, and inefficient thermal dissipation, through minimal-gain printing in the nanolaser. Moreover, our demonstration of the laser-on-waveguide structure emphasizes the integration benefits of this on-demand gain-printed Si nanolaser, highlighting its potential significance in the fields of Si photonics and photonic integrated circuits.